Adaptive control of radiated sound power based on time-domain estimates of acoustic radiation modes - Md Nor, Khairul Affendy; Mace, Brian R.; Hioka, Yusuke (International Institute of Acoustics and Vibration, IIAV, 2017)
In active structural acoustic control, broadband control of the radiated sound power from a structure can be achieved by minimizing the amplitudes of the acoustic radiation modes (ARMs). The shape of these ARMs is frequency dependent and only a few might radiate significant power in a given frequency range. In this paper a method is described by which the ARMs are estimated in real-time from a number of point response measurements taken on a vibrating structure. These estimates can be used to calculate the radiated power or, here, in a feedforward adaptive control system. Estimates of the ARM amplitudes in the time domain are produced by digitally filtering the outputs of an array of sensors mounted on the radiator. These filters are designed by FIR filters in the frequency domain based on the frequency-dependent ARMs and implemented in the time domain. These estimates are then used as the cost function in a feedforward, adaptive, filtered-X LMS controller. The theory is described with reference to a 2-dimensional vibrating structure. Finally numerical results of real-time simulations are presented.